Down-regulation of protein kinase C alpha/ezrin signals in light-induced phagocytic crisis of retinal pigment epithelium cells - Ya-Qiong Zhang; Yong-Gang Fan; Ya-Long Dang; Yan-Li Liu; Hua Liu; Li-Hua Li (International Journal of Ophthalmology, 2017)
AIM: To investigate the roles of PKC-α/ezrin signals in phagocytosis crisis of retinal pigment epithelium (RPE) cells in light damage model. METHODS: Light induced mice RPE injury model was established by continuously irradiating cool white light at different exposure time (0, 4, 8h light intensity: 4.18×10-6 J/cm2). In vitro, human ARPE-19 cells treated with the doses and intensity (1.57×10-6 J/cm2) of laser irradiation. Histology analysis was evaluated by hematoxylin and eosin (HE) staining. In vivo RPE phagocytosis was quantified by measuring the accumulation of photoreceptor outer segments in the sub-retinal space. In vitro RPE phagocytosis was assessed by calculating the relative fluorescence intensity of FITC-labeled microspheres in ARPE-19 cells. To further investigate the molecular mechanism, the activation of PKC-α/ezrin signal was evaluated by Western blot in vivo and in vitro. RESULTS: HE staining revealed that the thickness of outer nuclear layer decreased significantly after 4 and 8h light exposure. By immunostaining with rhodopsin, a significant greater accumulation of photoreceptor outer segment was noticed after light injury. In vitro, light injured RPE cells had less phagocytic activity in a dose dependent manner than that of the normal control (P<0.01). Western blot suggested the activation of PKC-α/ezrin signaling was down-regulated in a dose-dependent manner after light exposure. CONCLUSION: Our data suggest that light induced phagocytic crisis of RPE cells may result from the down-regulation of PKC-α/ezrin signaling.